Efektivitas Inovasi â€œOne Day Serviceâ€ Dalam Penerbitan Akta Kelahiran di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Tabanan - Felisa Rizky Amalia (Universitas Warmadewa, 2020)
The â€œONE DAY SERVICEâ€ innovation is an innovation to accelerate the birth certificate in collaboration with hospitals within a one-day publishing speed. The â€œONE DAY SERVICEâ€ innovation is an effort made Office of Civil Registry and Population, Tabanan Regency's in increasing the coverage of birth certificate ownership at the age of 0-18 years in Tabanan District which is relatively low. The â€œONE DAY SERVICEâ€ innovation collaborates with three hospitals in Tabanan Regency including the Kasih Ibu Tabanan Hospital, Cahaya Bunda Mother and Child Hospital and the Tabanan Regional General Hospital. Problem in this study is How Effectiveness of â€œONE DAY SERVICEâ€ Innovation in the Population and Civil Registry Office of Tabanan Regency? and What are the supporting and inhibiting factors of â€œONE DAY SERVICEâ€ innovation in the Tabanan Regency Population and Civil Registry Office?. This study using 8 variable of effectiveness scale theory according to S.P Siagian and distructive innovation theory according to Clayton M. Christensen and Joseph Bower. This research method using qualitative method with descriptive design .